Groundwater flow modeling in an intermontane basin (Journal of Nepal Geological Society, 2015)
Groundwater model has become a commonly used tool to perform various tasks. Geological, hydrogeological and geophysical data is required for constructing 3D hydrogeological framework models. Most of the time, it is realised that there is lack of sufficient data to build a groundwater model. The present work has been achieved after systematic data collection and hydrogeological study of Nara Basin, west Japan. Groundwater has been widely exploited for drinking water supply as well as for recreation purpose as Thermal Springs in the Nara Basin. There are hundreds of wells drilled in unconsolidated sediments and some tens of deep wells encountering the fractured basement. When water is exploited from a groundwater basin, it is necessary to understand properly the groundwater flow in different aquifer zones in the basin. Hydrostratigraphic units in the unconsolidated sediments overlying the basement rocks were established by using the borehole log data. In order to have understanding of the three dimensional configuration of these units, fence diagram was constructed. The geological and hydrogeological information were used to develop a conceptual model which was further calibrated and an acceptable model was obtained. The model was validated by comparing the observed and simulated heads and discharge.